FORTMED 2025. International Conference on Modern Age Fortifications of the Mediterranean coast (diségno, 2025)
Since its first edition in 2015, hosted by the Universitat Politècnica de València (Spain), the international FORTMED conference –dedicated to the study of Mediterranean fortifications– has established itself as a key annual event for the academic and scientific community. [read more]